Emergent biomarker derived from next-generation sequencing to identify pain patients requiring uncommonly high opioid doses - Kringel, D.; Ultsch, A.; Zimmermann, M.; Jansen, J. P.; Ilias, W.; Freynhagen, R.; Grießinger, Norbert; Kopf, A.; Stein, C.; Doehring, A.; Resch, E.; Lötsch, J. (Pharmacogenomics Journal, 2016)
Next-generation sequencing (NGS) provides unrestricted access to the genome, but it produces 'big data' exceeding in amount and complexity the classical analytical approaches. We introduce a bioinformatics-based classifying biomarker that uses emergent properties in genetics to separate pain patients requiring extremely high opioid doses from controls. Following precisely calculated selection of the 34 most informative markers in the OPRM1, OPRK1, OPRD1 and SIGMAR1 genes, pattern of genotypes belonging to either patient group could be derived using a k-nearest neighbor (kNN) classifier that provided a diagnostic accuracy of 80.6±4%. This outperformed alternative classifiers such as reportedly functional opioid receptor gene variants or complex biomarkers obtained via multiple regression or decision tree analysis. The accumulation of several genetic variants with only minor functional influences may result in a qualitative consequence affecting complex phenotypes, pointing at emergent properties in genetics.The Pharmacogenomics Journal advance online publication, 3 May 2016; doi:10.1038/tpj.2016.28.
EVALuna2:16735